PENGARUH MODEL PEMBELAJARAN DIATUR SENDIRI TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 11 PALEMBANG - Mizia Elliza; M. Djahir Basir; Deskoni Deskoni (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2014)
This study aims to determine the effect of self-regulated learning model with problem-based learning model on student learning outcomes in SMA Negeri 11 Palembang. This research problem whether there is any difference of influence of self-regulated learning model with problem-based learning model to student learning outcomes in SMA Negeri 11 Palembang. This research is an experimental research with pretest-posttest control group design research design. The population in this research is all the students of class X in SMANegeri 11 Palembang consisting of seven classes which amounted to 305 students. The sampling technique was taken by Cluster Random Sampling, so selected X.5 class as experiment class and class X.6 as control class. Data collection techniques used tests to measure student learning outcomes and observation aims to observe the learning process takes place. The statistic used is parametric statistic through t-test thus it can be concluded that there is difference of influence of model of learning arranged by itself with problem-based learning model to student learning result at Economic subject at SMA Negeri 11 Palembang. Therefore it is suggested to the teacher in order to apply the self-regulated learning model in the learning process so as to improve student learning outcomes.